MODEL PENETRASI PASAR "ALTERNATIF" (FATR TRADE}: Kasus Kerajinan Berbasis Sistem "Putting-out" di Klaster Sragen, Surakarta, Klatendon So/atigo - Arianti Ina R. Hunga; Tundjung Mahatma (JURNAL LITBANG PROVINSI JAWA TENGAH, 2008)
Research findings show that artisans' role in the 'putting-out' system is obviously substantial in supporting the batik and handicraft industry to survive the multi-dimensional crises in Indonesia, but ironically they are marginalised in the system. While the 'free trade' has caused disadvantages to micro-zsmall-scale producers, complex internal problems are also found, leading to marginalisation and poor performance in the bargaining power, production and productivity, business continuity, gender issues, and environmental issues. There are also problems concerning labour forces as home-workersorenot recognised nor protected by the Labour Law, and also limited knowledge on innovationand technology. The goal of action research is to promote the bargaining position of the producers in the business network through the fair trade. As a pilot project. this research focuses on finding access and ways to penetrate the alternative market (Fair Tracie) hy addressing three aspects, namely (1) reorganisation of the production system and the marketing: (2) transfer of innovation in the 'alternative' market product development; (3) implementation of the internet-based infmmationsystem conforming to the fair trade principles, The approach ofthe research treats the system as production clusters stressing on group dynamics.and the method is participatory action research withgender perspectives. The outcomes of the first (of two) stage show that ( l) the method needs to integrate marketing with gender-perspective empowerment aspects: (2) institutional set-up is to be done on two levels of different functions: production and marketing; (3) producers' capacity building is required through institutionalisation of organisation basics. group work. entrepreneurship. and fair trade values; (4) fair-trade• oriented innovation and technology transfer is needed in the product development and market information system; (5) network development applying fair trade principles is required to build common strength; (6) policies are 10 be made for the empowerment and protection o flhe home-working artisans.